Identifying Minahasa and Manado Society's Environmental Awareness with Cooper's Ecological Concept - Ceisy Nita Wuntu (Soegijapranata Catholic University, 2020)
Abstract : The objective of this writing is to expose the contextual implication of Ruckert's Ecocriticism in Figuring out The environmental awareness of Minahasanese and Manadonese in The Context of Cooper's Ecological Concept In The Leatherstocking Tales. This is an ethnografical study applying William Ruckert’s theory of literature that promotes a significant power in attaining the society’s sustainable life. Ruckert sees the power hidden in every works of literature. The argumentation is derived from ecological theory that regards all things in the universe interrelated. A work of literature according to him hides a power that is essential to help realizing the sustainable life, to help the world when the work is understood well. It is the responsible of the literaturists to figure out the messages, the voice in it, and the real power to be contributed to the society. Ruckert conseiders that the society where the idea in a work of literature comes is interrelated to writer, to work, to critics, to teachers and to researchers. It is from this concept, the research comes to be applied in formulating the society’s environmental awareness, understanding James Fenimore Cooper’s ecological concept in The Leatherstocking Tales as a hyrarchy of love, respect, wisdom and justice. the intellectual documents hidden in works of literature applied to reveal the society of Manado and Minahasa’s environmental awareness. The application of Ruckert’s theory in investigating the power as in The Leathestocking Tales explains that Minahasa and Manado society are not aware yet about the importance of maintaining their environment for a sustainable life as mentioned by Cooper. The society’s attitude and behaviour to their environment understood from their everyday life haven’t met yet with the perception about life requirement that they have. This is told by the way they give priority, their spirit and their motivation in doing what they know. Mostly they know much the requirements of a healty environment but they have no motivation in doing of what they know moreover they did not want to know about what is happening in their surrounding viewing from their knowledge about recent global environment.